Evergreen with Readings: A Guide to Writing - Fawcett, Susan and Sandberg, Alvin (Boston Houghton Mifflin Company, 1996)
Evergreen with Readings combines in one volume the new Fifth Edition of our popular college writing text Evergreen and fifteen high-interest reading selections. Based on our classroom experience at Bronx Community College of the City University of New York, Evergreen was designed for students who need to improve the writing skills so necessary to success in college and in most careers.
Keywords: Writing